1998
DOI: 10.1016/s0893-133x(98)00037-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Serotonin-2 Receptor Agonist or Antagonist Administration on Serotonin-1A Receptor Sensitivity

Abstract: We have investigated the effect of 5-HT 2 receptor agonist or antagonist administration on postsynaptic 5-HT 1A receptor sensitivity assessed by two behavioral measures, reciprocal forepaw treading or hypothermia induced by acute injection of the 5-HT 1A receptor agonist 8-OH-DPAT. The effectiveness of these drug treatments to downregulate 5-HT 2A receptors was confirmed by measuring the binding of [ 3 H]-ketanserin in cortical homogenates, because all of these drug treatments have been shown to result in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Our previous studies in rats indicate that a single administration of the 5-HT 2A receptor agonist DOI induces a functional desensitization of 5-HT 1A receptors that regulate the secretion of ACTH and oxytocin. Studies from other laboratories (Hensler and Truett, 1998;Valdez et al, 2002) indicate that repeated daily injections of DOI also produce a desensitization of 5-HT 1A receptor-induced hypothermia. Furthermore, repeated daily injections of DOI reduce the coupling between 5-HT 1A receptors and G proteins in the anterior cingulate cortex (Valdez et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous studies in rats indicate that a single administration of the 5-HT 2A receptor agonist DOI induces a functional desensitization of 5-HT 1A receptors that regulate the secretion of ACTH and oxytocin. Studies from other laboratories (Hensler and Truett, 1998;Valdez et al, 2002) indicate that repeated daily injections of DOI also produce a desensitization of 5-HT 1A receptor-induced hypothermia. Furthermore, repeated daily injections of DOI reduce the coupling between 5-HT 1A receptors and G proteins in the anterior cingulate cortex (Valdez et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Studies in cell culture and in vivo suggest that a two-way interaction exists between 5-HT 1A and 5-HT 2A receptors (Darmani et al, 1990;Pranzatelli and Pluchino, 1991;Eison et al, 1993;Eison and Mullins, 1995;Maswood et al, 1996;Hensler and Truett, 1998;Krebs-Thomson and Geyer, 1998;Valdez et al, 2002). One study indicates that 5-HT 1A and 5-HT 2A receptors are expressed by neurons in the frontal cortex (Martin-Ruiz et al, 2001).…”
mentioning
confidence: 99%
“…The regulation of the 5-HT 2A receptor, however, does not appear to follow the pattern established for many other G protein-coupled receptors. Repeated administration of agonists (Buckholtz et al, 1988;Anji et al, 2000) as well as antagonists (Blackshear and Sanders-Bush, 1982;Gandolfi et al, 1985;Hensler and Truett, 1998) results in the desensitization and down-regulation of central 5-HT 2A receptors.Given the interest in the role of the 5-HT 2A receptor in the action of many psychoactive drugs and the apparent anomalous regulation of 5-HT 2A receptors by antagonists, including atypical neuroleptics and many antidepressant drugs (Eison et al, 1991;Kuoppamaki et al, 1995), a thorough understanding of the mechanisms that regulate 5-HT 2A receptor function is desirable. In the current study, we have examined the effect of both agonist and antagonist exposure on 5-HT 2A receptor function in C6 glioma cells.…”
mentioning
confidence: 99%
“…The regulation of the 5-HT 2A receptor, however, does not appear to follow the pattern established for many other G protein-coupled receptors. Repeated administration of agonists (Buckholtz et al, 1988;Anji et al, 2000) as well as antagonists (Blackshear and Sanders-Bush, 1982;Gandolfi et al, 1985;Hensler and Truett, 1998) results in the desensitization and down-regulation of central 5-HT 2A receptors.…”
mentioning
confidence: 99%
“…Pharmacological action of agonists or antagonists binding to a receptor can regulate its functional levels (Fone et al, 1998;Kokay and Mercer, 1997;Welner et al, 1989). For example, it has been shown that 5-HT 1A receptors will be desensitized when either an agonist or antagonist is present (Hensler and Truett, 1998). In our laboratory, we have shown alterations in the physiological sensitivity to exogenous application of 5-HT at the crayfish neuromuscular junctions after altering levels of endogenous 5-HT as well as for chronic exposure of a 5-HT agonist .…”
Section: Discussionmentioning
confidence: 80%